Phenolic Extracts from Clerodendrum volubile Leaves Inhibit Cholinergic and Monoaminergic Enzymes Relevant to the Management of Some Neurodegenerative Diseases. (4th May 2017) - Oboh, Ganiyu; Ogunruku, Omodesola O.; Oyeleye, Sunday I.; Olasehinde, Tosin A.; Ademosun, Ayokunle O.; Boligon, Aline Augusti
ABSTRACT: This study investigated the inhibitory effects of phenolic-rich extracts from Clerodendrum volubile leaves on cholinergic [acetylcholinesterase (AChE) and butyrylcholinesterase (BChE)] and monoaminergic [monoamine oxidase (MAO)] enzymes' activities and pro-oxidants [Fe 2+ and quinolinic acid-(QA)] induced lipid peroxidation in rats brain homogenates in vitro. Free phenolic extracts (FPE) and bound phenolic extracts (BPE) were obtained via solvent extraction, and the total phenol and flavonoid contents were evaluated. The phenolic constituents of the extracts were also determined using high performance liquid chromatography coupled with diode array detector (HPLC-DAD). Our findings revealed that FPE had higher AChE (2.06 μg/mL), BChE (2.79 μg/mL), and MAO (2.81 μg/mL) inhibitory effects than BPE [AChE, 2.80 μg/mL; BChE, 3.40 μg/mL; MAO, 3.39 μg/mL]. Furthermore, FPE also had significantly ( P < 0.05) higher inhibitory effects on Fe 2+ and QA-induced lipid peroxidation compared to BPE. FPE (162.61 mg GAE/g) had higher total phenol content than BPE. However, BPE (18.65 mg QE/g) had significantly higher total flavonoid content than FPE (13.32 mg QE/g). Phenolic acids (such as gallic acid, catechin, chlorogenic, caffeic, ellagic, p-Coumaric acids) and flavonoids (catechins, rutin and quercetin) were present in both extracts. This study revealed that the enzymes' inhibitory activities and antioxidant potentials of phenolic-rich extracts from C. volubile could be part of the mechanism of actions behind its use for memory/cognitive function as obtained in folklore. However, FPE exhibited significantly higher enzymes, inhibitory and antioxidant potentials than BPE.